2012
DOI: 10.1007/s00592-012-0406-1
|View full text |Cite
|
Sign up to set email alerts
|

Nonalcoholic fatty liver and metabolic syndrome in Italy: results from a multicentric study of the Italian Arteriosclerosis society

Abstract: Nonalcoholic fatty liver disease (NAFLD) is associated with all the components of metabolic syndrome (MS) and might to be considered an additional component of MS itself. The Italian Society for the Study of Atherosclerosis (SISA) in 2005 started a research project aimed to study the NAFLD, using ultrasound (US), in nondiabetic MS subjects matching at least one of the ATP III criteria for HDL-C or triglycerides [TG]. Prevalence of US-NAFLD and its associated risk factors and prevalence of hypertransaminasemia … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
28
0
4

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(38 citation statements)
references
References 39 publications
6
28
0
4
Order By: Relevance
“…However, all the studies conducted so far have the limitation of being retrospective and performed with older generation ultrasound equipment. In our study, the value, using Landis's score, ranged between 0.79 and 1, which suggests that ultrasound has a good degree of reproducibility in defining the different echo patterns of liver cirrhosis, when it is performed by expert operators with specific training using up-to-date equipment as already demonstrated in previous US studies [21,24] and according to what is recommended by current guidelines [1].…”
Section: Discussionsupporting
confidence: 73%
See 2 more Smart Citations
“…However, all the studies conducted so far have the limitation of being retrospective and performed with older generation ultrasound equipment. In our study, the value, using Landis's score, ranged between 0.79 and 1, which suggests that ultrasound has a good degree of reproducibility in defining the different echo patterns of liver cirrhosis, when it is performed by expert operators with specific training using up-to-date equipment as already demonstrated in previous US studies [21,24] and according to what is recommended by current guidelines [1].…”
Section: Discussionsupporting
confidence: 73%
“…Before the study, the ultrasound operators agreed on general roles to follow in the procedure of examination, and they participated in a short training program according to previous ultrasound studies performed in other training [21,24].…”
Section: Abdominal Ultrasound Ultrasound (Us) Examinationsmentioning
confidence: 99%
See 1 more Smart Citation
“…The two major available studies, conducted on a large cohort of Italian patients with T2DM, reported NAFLD prevalence of 60-70% 33,34 ; data from the UK suggests that NAFLD, detected ultrasonographically, is present in 42.6% of patients with T2DM 35 . Prevalence of NAFLD also increases with BMI, such that in an unselected Italian population sample 91% of patients who were obese (BMI ≥30 kg/m 2 ), 67% of those who were overweight (BMI 25-30 kg/m 2 ) and 25% of individ uals at a normal weight (BMI 18-25 kg/m 2 ) had ultra sonographical evidence of NAFLD 36 .…”
Section: Nafld In Europementioning
confidence: 99%
“…Prevalence of NAFLD also increases with BMI, such that in an unselected Italian population sample 91% of patients who were obese (BMI ≥30 kg/m 2 ), 67% of those who were overweight (BMI 25-30 kg/m 2 ) and 25% of individ uals at a normal weight (BMI 18-25 kg/m 2 ) had ultra sonographical evidence of NAFLD 36 . The prevalence of NAFLD among patients matching at least one of the Adult Treatment Panel III (ATP III) criteria for serum lipid level alterations is similarly high at 78.8% 33 .…”
Section: Nafld In Europementioning
confidence: 99%